Theorem Jokes

  • Funny Jokes

    It all makes sense now...Dilbert's "Salary Theorem" states that "Engineers and scientists can never earn as much as business executives, sales people, accountants and especially liberal arts majors." This theorem can now be supported by a mathematical equation based on the following two well known postulates:Postulate 1: Knowledge is Power.
    Postulate 2: Time is Money.
    As every engineer knows: Power = Work / Time.Since: Knowledge = Power,
    then Knowledge = Work / Time,
    and Time = Money,
    then Knowledge = Work / Money.Solving for Money, we get: Money = Work / Knowledge.Thus, as Knowledge approaches zero, money approaches infinity, regardless of the amount of work done.

    Theorem. Every positive integer is interesting.

    Proof. Assume towards a contradiction that there is an uninteresting positive integer. Then there must be a smallest uninteresting positive integer. But being the smallest uninteresting positive integer is interesting by itself. Contradiction!

    Proof by example:
    The author gives only the case n = 2 and suggests that it contains most of the ideas of the general Proof.
    Proof by intimidation:
    Proof by vigorous handwaving:
    Works well in a classroom or seminar setting.
    Proof by cumbersome notation:
    Best done with access to at least four alphabets and special symbols.
    Proof by exhaustion:
    An issue or two of a journal devoted to your Proof is useful.
    Proof by omission:
    'The reader may easily supply the details'
    "The other 253 cases are analogous"
    Proof by obfuscation:
    A long plotless sequence of true and/or meaningless syntactically related statements.
    Proof by wishful citation:
    The author cites the negation, converse, or generalization of a theorem from the literature to support his claims.
    Proof by funding:
    How could three different government agencies be wrong?
    Proof by eminent authority:
    "I saw more...

    Theorem: log(-1) = 0Proof: a. log[(-1)^2] = 2 * log(-1)On the other hand: b. log[(-1)^2] = log(1) = 0Combining a) and b) gives: 2* log(-1) = 0Divide both sides by 2: log(-1) = 0

    Theorem: 1 = -1
    1 = sqrt(1) = sqrt(-1 * -1) = sqrt(-1) * sqrt(-1) = 1^ = -1
    Also one can disprove the axiom that things equal to the same thing are equal to each other.
    1 = sqrt(1)
    -1 = sqrt(1)
    Therefore 1 = -1
    As an alternative method for solving:
    Theorem: 1 = -1
    => 0/0=1/1=1

  • Recent Activity